(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2019)
The increasing rate of urbanization and continuous developments are the main factor which led to heavy metals contamination into the environment especially in the water bodies. However, the contamination of heavy metal can be treated using adsorption process using activated carbon. Thus, this study was based on using powdered activated carbon, which prepared from foxtail palm fruit and chemically activated using potassium hydroxide and phosphoric acid. The main parameters such as effect of chemical activating agent, effect of initial concentration of heavy metal and effect of sorbent dosage that influenced the sorption process were studied. From the result, activated carbon that was chemically activated by phosphoric acid shown the best removal compared to activated carbon that was chemically activated by potassium hydroxide. The percentage removal of Pb(II), Fe(II) and Zn(II) were 95.8%, 99.9% and 22.8% respectively using 0.5 g of activate carbon. The result indicates that the adsorption process using activated carbon that produced from plant can be applied for heavy metal removal from aqueous solution.